Overview of the Semiconductor Photocathode Research in China - Huamu Xie (MDPI AG, 2021)
With the growing demand from scientific projects such as the X-ray free electron laser (XFEL), ultrafast electron diffraction/microscopy (UED/UEM) and electron ion collider (EIC), the semiconductor photocathode, which is a key technique for a high brightness electron source, has been widely studied in China. Several fabrication systems have been designed and constructed in different institutes and the vacuum of most systems is in the low 10−8 Pa level to grow a high QE and long lifetime photocathode. The QE, dark lifetime/bunch lifetime, spectral response and QE map of photocathodes with different kinds of materials, such as bialkali (K2CsSb, K2NaSb, etc.), Cs2Te and GaAs, have been investigated. These photocathodes will be used to deliver electron beams in a high voltage DC gun, a normal conducting RF gun, and an SRF gun. The emission physics of the semiconductor photocathode and intrinsic emittance reduction are also studied.